2020
DOI: 10.1016/j.hpb.2019.06.019
|View full text |Cite
|
Sign up to set email alerts
|

The risk of not receiving adjuvant chemotherapy after resection of pancreatic ductal adenocarcinoma: a nationwide analysis

Abstract: Background:The relation between type of postoperative complication and not receiving chemotherapy after resection of pancreatic ductal adenocarcinoma (PDAC) is unclear. The aim was to investigate which patient factors and postoperative complications were associated with not receiving adjuvant chemotherapy.Methods: Patients who underwent resection (2014)(2015)(2016)(2017) for PDAC were identified from the nationwide mandatory Dutch Pancreatic Cancer Audit. The association between patient-, tumor-, center-, trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 38 publications
4
59
0
Order By: Relevance
“…In the Prodige study, a RCT comparing a modified FOLFIRINOX regimen with gemcitabine in the adjuvant setting found an impressive median survival of 54 months with mFOLFIRINOX (29). Unfortunately, there is a significant fraction of patients who undergo upfront surgery but do not recover adequate functional status to receive adjuvant therapy and its treatment benefits (80).…”
Section: Neoadjuvant Treatment In Resectable Pdacmentioning
confidence: 99%
“…In the Prodige study, a RCT comparing a modified FOLFIRINOX regimen with gemcitabine in the adjuvant setting found an impressive median survival of 54 months with mFOLFIRINOX (29). Unfortunately, there is a significant fraction of patients who undergo upfront surgery but do not recover adequate functional status to receive adjuvant therapy and its treatment benefits (80).…”
Section: Neoadjuvant Treatment In Resectable Pdacmentioning
confidence: 99%
“…The exact reason as to why a smaller proportion of patients in cohort A received adjuvant chemotherapy is unclear, however substantial variation of adjuvant chemotherapy rates for patients with pancreatic head carcinoma among different centers have been described. 20,21 In the present study, patients with PALN involvement who underwent resection had a median overall survival of 11 months, compared with 7 months in patients where resection was avoided (p = 0.049). In a smaller subgroup of patients with PALN involvement who received adjuvant chemotherapy, the median overall survival was 13 months after pancreatoduodenectomy, compared with 11 months after a palliative bypass procedure (p = 0.033).…”
Section: Discussionmentioning
confidence: 54%
“…Although these studies have led to an improved quality of care worldwide, pancreatic fistula still remains one of the most feared complications after pancreatic surgery. When not recognized early, pancreatic fistula may have major impact on the clinical course and is associated with an increased risk of in-hospital death, prolonged hospital stay, lower chance of receiving adjuvant chemotherapy and impaired long-term survival [3,5,42]. A recent study showed that the difference in clinical outcome in Dutch centers can be explained in difference in failure to rescue rate rather than incidence of major complications [11].…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic resection is, however, a major abdominal operation which is associated with a 50% risk of complications [2]. Complications are associated with postoperative death and reduced long-term survival because patients with a complicated postoperative course are often unfit to receive adjuvant chemotherapy [3][4][5].…”
Section: Introductionmentioning
confidence: 99%